Contemplative Reflective Practice, Conocimiento, and Continuing Medical Education - Barbara Shaw Anderson (Adult Education Research Conference, 2006)
Contemplative reflective practices, exemplified by Remen and Kabat-Zinn, nurture “subversive knowledges” that can help physicians and their educators address ethical issues in the health care system. Continuing medical education should encourage physicians to become what Varela terms “ethical experts.”
Keywords: Reflective practice; continuing medical education; meditation; ethics